Development of Authentic Assessment Instrument for Improving Extensive Capacity of Metacognitive Perspective - Fathurohman, Irfai; Cahyaningsih, Riyan Dwi (Asian Journal of Assessment in Teaching and Learning, 2021)
The purpose of this study is to find out the authentic assessment instrument factors in the ability to read English extensively from a metacognitive perspective. The study was designed with an instrument of developmental research design. The developmental research design refers to the research development proposed by Mardapi. The modification model of the Mardapi instrument development was carried out through three stages, i.e., preliminary stages, development stage and evaluation stage. The results of this study through exploratory factor analysis showed that there were three factors derived from 24 statement items. The loading factor value for each item in each factor is ˃ 0.3 which means that the whole item is valid. Based on the Alpha Cronbach reliability test it was obtained a value of 0.954, the instrument was declared reliable. The conclusion shows an authentic assessment instrument of extensive reading ability in English through metacognitive strategies for PBSI FKIP UMK students was proven to be valid, reliable and feasible to use. Authentic assessment instruments can improve the English reading skills of PBSI FKIP UMK students through a learning process that puts forward an approach according to the characteristics of each student.